Recent Advances in Electrocatalysts for Alkaline Hydrogen Oxidation Reaction - Zhao, Ruopeng; Yue, Xin; Li, Qinghua; Fu, Gengtao; Lee, Jong‐Min; Huang, Shaoming (Small (Weinheim an der Bergstrasse, Germany), 2021)
With the rapid development of anion‐exchange membrane technology and adequate supply of high‐performance non‐noble metal oxygen reduction reaction (ORR) catalysts in alkaline media, the commercialization of anion exchange membrane fuel cells (AEMFCs) become possible. However, the kinetics of the anodic hydrogen oxidation reaction (HOR) in AEMFCs is significantly decreased compared to the HOR in proton exchange membrane fuel cells (PEMFCs). Therefore, it is urgent to develop HOR catalysts with low price, high activity, and robust stability. However, comprehensive timely reviews on this specific subject do not exist enough yet and it is necessary to update reported major achievements and to point out future investigation directions. In this review, the current reaction mechanisms on HOR are summarized and deeply understood. The debates between the mechanisms are greatly harmonized. Recent advances in developing highly active and stable electrocatalysts for the HOR are reviewed. Moreover, the side reaction control is for the first time systematically introduced. Finally, the challenges and future opportunities in the field of HOR catalysis are outlined. Current reaction mechanisms on hydrogen oxidation reaction (HOR) are summarized and deeply understood. The debates between the mechanisms are greatly harmonized. Recent advances in developing high‐activity and ‐stability catalysts for the HOR are reviewed. Moreover, the side reaction control is for the first time systematically introduced. Finally, the challenges and future opportunities in the field of HOR catalysis are outlined.